PENATAAN SARANA DAN PRASARANA KAWASAN PEMUKIMAN JALAN HIDAYAT DUSUN MERPATI DESA SUNGAI KAKAP: PENATAAN SARANA DAN PRASARANA KAWASAN PEMUKIMAN JALAN HIDAYAT DUSUN MERPATI DESA SUNGAI KAKAP - Abnur Kamala, Siti; Jannah, Miftahul; muhtadi, ahmad; Resky, Indah Anjar (RETENSI, 2023)
Many factors encourage the formation of a slum area, especially those in the Sungai Kakap area, Kubu RayaRegency, West Kalimantan. Apart form the geographical location, most slum areas are also caused byinadequate facilities and infrastructure. A slum environment is defined as an environment that is not feasibleor not in accordance with spatial planning. The government’s limitations in providing and facilitatingfacilities and infrastructure make people choose their own alternatives to maintain their lives. The purposeand benefit of writing this research is as a medium for channeling the aspirations of the community aboutfacilities and infrastructure that are still not well realized, so that the are becomes a healthy, comfortable andbeautiful area. In conducting research, data such as primary and secondary data are required. Primary datais obtained form surveys or observations made by the author directly in the field, while secondary data isobtained through local government agencies or institutions. The results of this research area in the form ofstructuring road network infrastructure, structuring a clean water network using a 5 m3 water tank for apopulation 13000 people in the next ten years, structuring waste network infrastructure by calculating thevolume of community waste, the number of TPS needs and transporting waste using carts in the area understudy.